(untitled) (Lundiana: International Journal of Biodiversity, 2002)
Samples of Laelapidae collected from wild and commensal rodents in Belo Horizonte, State of Minas Gerais, Brazil, and comprising nine operating taxonomic units were phenetically analyzed by using 44 characters of female mites. A phenogram indicated three clusters, with Androlaelaps rotundus (Fonseca, 1935) more closely related to Laelaps Koch, 1839 and Echinolaelaps Ewing, 1929 than to Androlaelaps foxi (Fonseca, 1957) and Androlaelaps fahrenholzi (Berlese, 1911). Systematic changes proposed as a result of this study include the revalidation of the genus Eubrachylaelaps Ewing, 1929 to include A. rotundus; the recognition of Echinolaelaps as a subgenus of Laelaps; at least, the division of the genus Androlaelaps Berlese, 1903 into two subgenera: Androlaelaps to include A. foxi and Haemolaelaps Berlese 1910 to include A. fahrenholzi.